Coseismic Uplift of the 1999 Mw7.6 Chi‐Chi Earthquake and Implication to Topographic Change in Frontal Mountain Belts. Issue 15 (3rd August 2020) - Chuang, R. Y.; Lu, C. H.; Yang, C. J.; Lin, Y. S.; Lee, T. Y.
Abstract: Large dip‐slip earthquakes have a major contribution to mountain building while earthquake‐induced landslides lower mountains simultaneously. The amount of the coseismic uplift and landslides may dominate long‐term mountain evolution. However, how earthquakes contribute to mountain evolution through coseismic uplift and landslides is less constrained in real cases. We present the regional coseismic uplift of the 1999 M w 7.6 Chi‐Chi earthquake by using synthetic aperture radar (SAR) images and GPS. The coseismic uplift pattern is consistent with field observations showing increasing movement to the north with ~8 m of uplift toward the northern end. We estimated uplifted rock volume of 2.60 ± 1.09 km 3, which is five times greater than the coseismic landslide volume. Intense erosion of the Taiwan orogen may erode elevated rocks rapidly, but the uplift and landslide distributions do not match and correlate more inversely, suggesting the frontal orogenic topography should be increased rather than annulled over earthquake cycles. Plain Language Summary: Earthquakes can raise mountains but they can cause landslides to lower the mountains at the same time. For large earthquakes, mountains could reduce the size due to more landslides than uplift. It is important to analyze earthquakes occurred within mountain ranges to examine how much volume of rocks is elevated and how much volume of rocks is trampled down. Because complete observations of uplift and landslides for large earthquakes are rare, we used geodetic methods to estimate the volume of the elevated rocks for one of the largest earthquakes in mountain ranges in the world, the Chi‐Chi, Taiwan, earthquake in 1999. The volume of elevated rocks is much larger than the landslide volume, and the uplift area is close to the frontal mountains and the landslide areas are distributed in the deeper mountains. If this finding holds for other mountain ranges in similar settings, this means that large earthquakes should raise mountains, especially in the frontal part of the mountains. Key Points: We estimate the regional pattern of the coseismic uplift of the Chi‐Chi earthquake Increased rock volume is significantly greater than coseismic landslide volume for the Chi‐Chi earthquake The distributions of coseismic uplift and landslides suggest differential topographic increase at frontal orogen